2020
DOI: 10.1186/s13756-019-0662-8
|View full text |Cite
|
Sign up to set email alerts
|

European intensive care physicians’ experience of infections due to antibiotic-resistant bacteria

Abstract: BackgroundAntimicrobial resistance (AMR) compromises the treatment of patients with serious infections in intensive care units (ICUs), and intensive care physicians are increasingly facing patients with bacterial infections with limited or no adequate therapeutic options. A survey was conducted to assess the intensive care physicians’ perception of the AMR situation in the European Union/European Economic Area (EU/EEA).MethodsBetween May and July 2017, physicians working in European ICUs were invited to comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
110
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(122 citation statements)
references
References 24 publications
6
110
1
Order By: Relevance
“…While the search for alternative antimicrobial agents that can effectively control the spread of multidrug resistance continues, various temporary measures are been employed for the treatment of infections caused by drug resistant bacterial isolates. Antibiotic combination therapy is a possible effective option which currently is attracting numerous research attention [ 34 36 ]. Combinations of antibiotics effectively inhibit microbial proliferation through a multi-target approach resulting in the microbial death.…”
Section: Resultsmentioning
confidence: 99%
“…While the search for alternative antimicrobial agents that can effectively control the spread of multidrug resistance continues, various temporary measures are been employed for the treatment of infections caused by drug resistant bacterial isolates. Antibiotic combination therapy is a possible effective option which currently is attracting numerous research attention [ 34 36 ]. Combinations of antibiotics effectively inhibit microbial proliferation through a multi-target approach resulting in the microbial death.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that physicians caring for critically ill patients perceived AMR to be a substantial problem, and their perception of ASP seemed favorable [ 24 , 25 ], but fear of treatment failure or a worse clinical outcome in critically ill patients may discourage physicians from de-escalating or discontinuing antimicrobial therapy despite inappropriate use. Hence, ASP in critical care settings is particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli is a gram-negative bacterium, which can cause intestinal (diarrhea) or extraintestinal (urinary tract infection, septicaemia, pneumonia, and meningitis) diseases in humans and animals (Cabal et al, 2016 ). Current antibiotic treatments used to treat E. coli often result in a spread of multidrug resistance (MDR) of E. coli (Lepape and Monnet, 2009 ). For example, E. coli strains produce Extended-Spectrum Beta Lactamase and metallo-β-lactamas, enzymes which make E. coli become resistant to several antibiotic drugs (Peña et al, 2006 ; Birgy et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%